(untitled) (Research, Society and Development, 2023)
Objective: To describe the clinical-nutritional and sociodemographic profile of patients on hemodialysis (HD) in a nephrology unit of a regional hospital in the Federal District. Methodology: This is a quantitative, descriptive, and cross-sectional research. The analyzed variables were age, sex, ethnic-racial identification, marital status, education level, family income, comorbidities, etiology of chronic kidney disease (CKD), duration of hemodialysis, type of vascular access for the procedure, dialytic efficiency through Kt/V and percentage of urea reduction (PRU), anthropometric parameters, and Global Subjective Assessment (ASG) using a seven-point scale. Results: A total of 33 patients participated, with the majority being adults (72.70%) and male (60.60%). A prevalent number of individuals had low education levels and a family income of only one minimum wage. The main etiologies and comorbidities presented were Diabetes Mellitus (DM) and Systemic Arterial Hypertension (SAH). The majority (73.9%) underwent HD through arteriovenous fistula. According to ASG, 63.64% were classified as well-nourished. When comparing male and female groups, there was statistical significance (p<0.05) for the variable’s Kt/V, PRU, and % of adequacy of arm muscle circumference. There was also a strong, direct, and positive correlation (>0.5) between ASG and anthropometric indicators. Conclusion: the most patients had an adequate nutritional status.